PENGARUH PENGUASAAN MATERI BILANGAN BULAT TERHADAP HASIL BELAJAR MATEMATIKA SISWA MATERI POKOK PECAHAN DI KELAS VII SMP NEGERI 1 BADIRI - delta pardede (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to know whether there is a significant influence integer mastery and students’ mathematic achievement on the topic fraction at the seventh grade students of SMP Negeri 1 Badiri. The research was conducted by using descriptive quantitative method with 32 students as the sample and they were taken by using total sampling technique. Test was used in collecting the data. Based on descriptive analysis, it could be found (a) the average of integer mastery was 71.09 (good category) and (b) the average of students’ mathematic achievement on the topic fraction was 77.97 (good category). Furthermore, based on inferential statistic by using ttest, the result showed ttable was less than tcalculated (1.697<5.68). It means, there is a significant influence integer mastery and students’ mathematic achievement on the topic fraction at the seventh grade students of SMP Negeri 1 Badiri.